Poradnikowy wymiar dyskursu naukowego wieków dawnych = The guide shape of academic discourse of past centuries - Rejter, Artur (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article the analysis of ancient academic discourse is described on the example of medical texts. The focus was on the advisory aspect of discourse which take different text shapes and constitute an important element of discourse. Furthermore, the guide aspects are the expressions of practical aspect of ancient academic texts.
Keywords: dyskurs naukowy; poradnik; styl; tekst; historia języka polskiego; academic discourse; guidebook; style; text; history of the Polish language